Expanding the Historical Narrative of Early Visual Modernity in Malaya - Sarena Abdullah (Wacana Seni Journal of Arts Discourse, 2018)
The history of Malaysian modern art early in the 20th century is not well-established. Also, the term "modern art" has yet to be extensively discussed locally. Evidently, the term does not refer to the modern art movements that occurred in Euramerica; rather, it frequently refers to a type of art that differs from its traditional counterparts and painting media that were alien to the indigenous people of the Malay Archipelago then. It is presumed that (1) modern art began in Malaysia – or Malaya in this context – just before the 1930s and that (2) visual appreciation of modern art among the Malays was only attained after the widespread adoption of painting media in Malaya. Hence, this paper examines the various sketches in Malay manuscripts and newspaper illustrations as some of these works were the initial forms of visual modernity during the 19th century, thus expanding the credence of the beginning of the history of Malaysian modern art to as early as the late 19th century.